2021
DOI: 10.1186/s12904-021-00756-9
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities for spiritual care practice in hospices in a middle-income country

Abstract: Background Spiritual care is a key component of palliative care, but it has been overlooked and understudied in low- and middle-income country contexts, especially in Africa. In this study we sought to establish what the current spiritual care practices are in hospice palliative care settings in South  Africa with a focused view on what spiritual care training is currently offered and what training needs still remain unmet. Methods We explored spir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Nonetheless, research has demonstrated that religious belief is a vital component of spiritual care needs and a means of expressing spirituality in and of itself. Patients who practice religion have better inner serenity [ 43 , 49 ]. Thus, the factors listed above contribute to indifference mainly focused on the “help thinking” and “help religious practice” dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, research has demonstrated that religious belief is a vital component of spiritual care needs and a means of expressing spirituality in and of itself. Patients who practice religion have better inner serenity [ 43 , 49 ]. Thus, the factors listed above contribute to indifference mainly focused on the “help thinking” and “help religious practice” dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of the need for sensitivity regarding culture, religion and ethnicity in palliative care interventions are currently gaining impetus in the global North as a specialised area (Cain, et al 2018 ; Curtis, 2019; Elk, et al 2020 ). Given SA’s history and divided society, however, issues of cultural and spiritual diversity, and race and racism, have long been core concerns in the development of health care interventions, including palliative care interventions (Baldwin-Ragaven, London, and De Gruchy 1999 ; De Beer and Chipps 2014 ; Drenth et al 2018 ; Swartz 1985 , 1998 ; Mahilall and Swartz 2021a ).…”
Section: Introductionmentioning
confidence: 99%